2017
DOI: 10.1016/j.jocn.2016.10.042
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tumor treating fields and temozolomide in MGMT expressing and non-expressing patient-derived glioblastoma cells

Abstract: A recent Phase 3 study of newly diagnosed glioblastoma (GBM) demonstrated the addition of Tumor Treating Fields (TTFields) to temozolomide (TMZ) after combined radiation/TMZ significantly increased survival and progression free survival. Preliminary data suggested benefit with both methylated and unmethylated O-6-methylguanine-DNA methyl-transferase (MGMT) promoter status. To date, however, there have been no studies to address the potential interactions of TTFields and TMZ. Thus, the effects of TTFields and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…Temozolomide (TMZ) is a DNA‐alkylating agent that causes lethal DNA lesions in fast‐dividing cancer cells . TMZ is widely used to treat primary or metastatic brain cancer, which had efficacy on the recovery of patients . It was reported that BIS or HSF1 knockdown combined with TMZ treatment increased tumour apoptosis while cancer stem‐like properties was suppressed, such as SOX2 protein expression .…”
Section: Introductionmentioning
confidence: 99%
“…Temozolomide (TMZ) is a DNA‐alkylating agent that causes lethal DNA lesions in fast‐dividing cancer cells . TMZ is widely used to treat primary or metastatic brain cancer, which had efficacy on the recovery of patients . It was reported that BIS or HSF1 knockdown combined with TMZ treatment increased tumour apoptosis while cancer stem‐like properties was suppressed, such as SOX2 protein expression .…”
Section: Introductionmentioning
confidence: 99%
“…The results of Clark et al [21] failing to demonstrate a synergistic effect between the alkylating agent TMZ, although significant, is not surprising. From a mechanistic standpoint, TTFields were shown to interfere with the spindle tubulin polymerization as a consequence of generating non-uniform intracellular fields that exert forces that move organelles and polar macromolecules, resulting in apoptotic cell death [11] .…”
Section: Commentarymentioning
confidence: 91%
“…Thus, to test the hypothesis that TTFields might exhibit a synergistic, or supra-additive interaction with TMZ, particularly in MGMT protein expressing GBM cells that are resistant to TMZ (modeling unmethylated MGMT GBM patients), investigators at the University of Wisconsin elected to address this question with an in vitro model (see figure 2). In view of the clinical relevance of these recently published results [21] , the review below summarizes these preclinical experiments:…”
Section: Research Highlightmentioning
confidence: 99%
See 1 more Smart Citation
“…In another randomized clinical trial of patients with glioblastoma who had received standard radiation and concomitant temozolomide chemotherapy, the addition of TTFields to maintenance temozolomide chemotherapy resulted in improved outcomes compared to those that received maintenance temozolomide alone 23 . Additionally, research has shown that TTFields work irrespective of patient MGMT promoter methylation status; therefore TTFields may constitute a clinical intervention that also works in patients with unmethylated MGMT status 24 . Taken together, these studies suggest broad implications on the effectiveness of TTFields for the treatment of glioblastomas.…”
mentioning
confidence: 99%